2012
DOI: 10.1177/0741932512448254
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Teaching Sentence-Level Writing Skills to Students With Writing Difficulties and Learning Disabilities

Abstract: Students with writing difficulties and learning disabilities struggle with many aspects of the writing process, including use of sentence-level skills. This literature review summarizes results from 19 published articles that used single-case or group-experimental and quasi-experimental designs to investigate effects of intervention on the sentence-level skills of handwriting, sentence construction, and grammar/usage. Results suggest struggling writers benefited from intervention, particularly in handwriting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 49 publications
10
75
0
5
Order By: Relevance
“…During prescreening, both students in Group 1, Fatima and Jim, showed the slowest handwriting performance of all students, 57 CLPM and 36 CLPM, respectively, transcribing text at approximately half or a quarter of the rate of students in the other three groups. Prior research has found that fluent handwriting at the sublexical and lexical levels of writing can impact overall text production (Berninger et al., ; Datchuk & Kubina, ). In addition, in accordance with cognitive theories of writing development (Graham, ), lack of proficiency with transcription skills can constrain working memory and hinder overall writing output.…”
Section: Discussionmentioning
confidence: 99%
“…During prescreening, both students in Group 1, Fatima and Jim, showed the slowest handwriting performance of all students, 57 CLPM and 36 CLPM, respectively, transcribing text at approximately half or a quarter of the rate of students in the other three groups. Prior research has found that fluent handwriting at the sublexical and lexical levels of writing can impact overall text production (Berninger et al., ; Datchuk & Kubina, ). In addition, in accordance with cognitive theories of writing development (Graham, ), lack of proficiency with transcription skills can constrain working memory and hinder overall writing output.…”
Section: Discussionmentioning
confidence: 99%
“…Comme premier constat, toutes les recensions antérieures consultées montrent que les stratégies d'enseignement éprouvées ou recommandées valent pour tous les types d'élèves, typiques et atypiques, mais démontrent un effet plus marqué chez ceux qui sont en difficulté ou qui présentent un trouble d'apprentissage (Datchuk et Kubina, 2012;Edmonds et al, 2009;Gillespie et Graham, 2014;Graham et Harris, 2009;Hongli, 2014;Kaldenberg et al, 2015;Rouhani et al, 2016;Scammacca et al, 2015). Plusieurs auteurs soulignent les difficultés rencontrées lorsqu'ils tentent d'analyser des résultats de recherches tantôt relatifs à des évaluations construites par les chercheurs, tantôt à des évaluations normatives (Kaldenberg et al, 2015;Scammacca et al, 2015;Wansek et al, 2010).…”
Section: L'analyse De Recensions Antérieures Période De 2012 à 2016unclassified
“…A number of meta-analyses examining the effects of interventions on the writing skills of students with LD have demonstrated that students with LD benefi t from explicit instruction in handwriting and sentence construction (Datchuk & Kubina, 2012 ) and in writing strategies and metacognitive self-regulation strategies throughout the writing process . A number of meta-analyses examining the effects of interventions on the writing skills of students with LD have demonstrated that students with LD benefi t from explicit instruction in handwriting and sentence construction (Datchuk & Kubina, 2012 ) and in writing strategies and metacognitive self-regulation strategies throughout the writing process .…”
Section: Writing Interventions For Els With Ldmentioning
confidence: 99%